Кому належала й куди підпорядковувалася Данина: чернігівське село у майновому та адміністративному поділі України - Тимошик, М. (Сiверянський лiтопис, 2015)
На прикладі села Данина Ніжинського району проаналізована історія майнової приналежності сільських населених пунктів Чернігівщини. Охарактеризовано періодичність,
сутність та результати адміністративних реформ, які здійснювалися на українських теренах у різні історичні епохи. На примере села Данина Нежинского района проанализирована история имущественной принадлежности сельских населенных пунктов Черниговщины. Дана характеристика периодичности, существа и результатов административных реформ, проводимых
на украинских землях в разные исторические эпохи. The history of property appurtenance of Chernihiv rural settlements has been analyzed on
the example of the Danyna village of Nizhyn district. The conditions under which the villages
were given or sold to new owners while the existence of Cossack Ukraine and then of it as a part
of Russia have been viewed as well.
The character, essence and the results of administrative reforms which were carried out on
the territory of Ukraine during different times have been analyzed. It deals mainly with the
regimental system of administration of Ukraine when villages were
subdued to Cossack squadrons and squadrons in terns were subdued to regiments. The
evolution of the administrative reforms introduced by the Russian government after Zaporizka
Sich and Cossack administrative system were finally destroyed has been viewed in this article.
Destructive influence of commune-bilshovyk experiments in terms of volost, povit liquidation
and village resubordinating during different district changes on the life of a Ukrainian village
has been accentuated.